O Lobo e o Morcego: A cultura popular e o imaginário inglês do século XIX - BRANCO, Arturo Alejandro Gonzales Y Rodrigues (2009)
This thesis was written to uncover the process were a cultural symbol of a political oppressed people gets in possession of their oppressors, is modified, inserted in their literary imaginary, and then used by the neocolonialist ideology to disqualify the oppressed people‟s culture. The vampire, in popular culture, represents the supreme evil, for them, the foreigners, which do not have the same religion and simbology, being cursed by their God and obligated to walk on the living world, even after death. Studding this character of the popular imaginary, the english intellectual Sabine Baring-Gould change and bring it to the Victorian England mass culture. The evil represented by the vampire is no more the one that was exotic for the Balcanic people, but the foreigner for the english perspective, the uncivilized natives from the colonies. Based in Sabine Baring-Gould, Bram Stoker wrote his gothic fiction book, Drácula, as a way to propagate, for the Victorian citizens, the neocolonialist values of chastity, honor, civilization and xenophobia. Stoker‟s book, besides being a very popular entertainment book, is also famous for the exaltations to the civilized world denizen, the inhabitant of the colonial potencies, in their dominance relationship over the colonial people, the inhabitants of the dark corners of the world, presenting them as monsters capable of the worst depravations